INTERSECTIONALITY OF STRATEGIC THINKING AND EVIDENCE-BASED DEFENSE POLICY MAKING - Sarjito, Aris; Saputro, Guntur Eko (Jurnal Governansi, 2024)
In an era characterized by rapid geopolitical shifts and evolving security threats, the imperative for evidence-based defense policymaking has never been more pressing. This research delves into the intricate nexus between strategic thinking and empirical evidence in defense policy formulation, seeking to address key gaps in understanding and practice. Through a qualitative analysis of secondary data encompassing scholarly literature, governmental reports, and defense policy documents, this study elucidates the fundamental elements of strategic thinking within defense policymaking frameworks and examines their current integration with empirical evidence. The research findings shed light on the pivotal role of strategic foresight, threat assessment methodologies, and resource allocation strategies in shaping defense policy. Moreover, the study explores the impact of intersectionality, encompassing factors such as geopolitical dynamics, technological advancements, and socioeconomic disparities, on the effectiveness of strategic thinking and the utilization of empirical evidence in defense policy making processes. The novelty lies in the comprehensive exploration of intersectionality’s impact on defense policy formulation and the identification of guiding principles to enhance the integration of strategic thinking and empirical evidence. The research underscores the need for a holistic approach that acknowledges and addresses the multifaceted nature of contemporary security challenges.